Histopathological Evidence of Nephrotoxicity in Mice Administered Arcangelisia flava (L.) Merr. Stem Extract from Enggano Island - Nurul Kamilah, Santi; Muslim, Choirul; Hermawati, Ely; Maulana, Sherlo Adha; Fita Lestari, Dian; Sri Astuti, R.R.; Ezer Simanungkalit, Eben; Siti Fitri Andriyani, Eka; Ananda Putri, Dea (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2026)
Arcangelisia flava (L.) Merr., an endemic Indonesian forest plant, is traditionally consumed as an aphrodisiac by the Enggano Island community, yet its safety profile remains poorly documented. This study evaluated the nephrotoxic potential of A. flava stem extract using a murine model. Fifteen ICR mice were randomly assigned to a control group receiving distilled water and a treatment group receiving 200 mg/kg body weight of ethanolic stem extract orally for 14 days. Kidney tissues were processed for hematoxylin-eosin staining and semi-quantitative histopathological scoring. Compared with controls, treated mice showed higher damage scores in the glomerulus, proximal tubule, and distal tubule, along with a reduction in glomerular diameter. Histopathological findings included podocytopenia, widened Bowman’s space, proximal tubular brush border loss, apoptotic changes, and ablation of macula densa and distal tubular epithelial cells. These findings indicate nephrotoxic activity of A. flava stem extract and highlight the need for dosage standardization before use. Bukti Histopatologis Nefrotoksisitas pada Tikus yang Diberikan Arcangelisia flava (L.) Merr. Ekstrak Batang dari Pulau Enggano ABSTRAK: Arcangelisia flava (L.) Merr. merupakan tumbuhan endemik hutan Indonesia yang secara tradisional dimanfaatkan sebagai afrodisiak oleh masyarakat Pulau Enggano, namun aspek keamanannya masih belum terdokumentasi dengan baik. Penelitian ini bertujuan mengevaluasi potensi nefrotoksik ekstrak batang A. flava menggunakan model mencit. Sebanyak 15 ekor mencit jantan galur ICR dibagi acak ke dalam kelompok kontrol yang diberi akuades dan kelompok perlakuan yang diberi ekstrak etanol batang A. flava dosis 200 mg/kg bobot badan secara oral selama 14 hari. Jaringan ginjal diproses dengan pewarnaan hematoksilin-eosin dan dianalisis menggunakan skor kerusakan histopatologi semi-kuantitatif. Dibandingkan kontrol, kelompok perlakuan menunjukkan skor kerusakan lebih tinggi pada glomerulus, tubulus proksimal, dan tubulus distal, serta penurunan diameter glomerulus. Temuan histopatologi meliputi podositopenia, pelebaran ruang Bowman, hilangnya brush border tubulus proksimal, perubahan apoptosis, serta ablasi makula densa dan sel epitel tubulus distal. Hasil ini menunjukkan aktivitas nefrotoksik ekstrak batang A. flava.